2020
DOI: 10.1038/s41419-020-03096-3
|View full text |Cite
|
Sign up to set email alerts
|

RNF180 mediates STAT3 activity by regulating the expression of RhoC via the proteasomal pathway in gastric cancer cells

Abstract: Ring finger protein 180 (RNF180) is an important member of the E3 ubiquitin ligase family. As a tumor suppressor gene, RNF180 is significantly associated with the prognosis of patients with gastric cancer (GC) and can inhibit the proliferation, invasion, and migration of GC cells. Signal transducer and activator of transcription 3 (STAT3) are considered one of the most common oncogenes in human cancers with a key role in GC progression. In this study, we explored the molecular signaling pathways by which RNF18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Through using of the online GEPIA database and IHC staining of 135 GC tissues from our center, we found a significant positive correlation between the expression of RNF180 and ADAMTS9. According to our previous studies, RNF180 is a suppressor gene that inhibits LN metastasis in GC and could act as an independent prognostic indicator of gastric cancer 19 , 25 . RNF180 is an E3 ubiquitin ligase that belongs to the ubiquitin-proteasome system and plays an important role in post-translational modification, which actually influence several processes of oncogenesis and tumor progression 26 .…”
Section: Discussionmentioning
confidence: 97%
“…Through using of the online GEPIA database and IHC staining of 135 GC tissues from our center, we found a significant positive correlation between the expression of RNF180 and ADAMTS9. According to our previous studies, RNF180 is a suppressor gene that inhibits LN metastasis in GC and could act as an independent prognostic indicator of gastric cancer 19 , 25 . RNF180 is an E3 ubiquitin ligase that belongs to the ubiquitin-proteasome system and plays an important role in post-translational modification, which actually influence several processes of oncogenesis and tumor progression 26 .…”
Section: Discussionmentioning
confidence: 97%
“…These observations indicated that miR-301a-3p was a suppressor of STAT3 protein expression and the JAK/STAT signaling pathway in TPC-1 cells. STAT3 is considered to be one of the most common oncogenes in human cancers and plays a key role in PTC progression ( 17 , 55 ). It was further demonstrated that curcumin and miR-301a-3p mimics reduced the levels of phosphorylated JAK1, JAK2, JAK3, STAT1 and STAT2 via the targeting of STAT3 by miR-301a-3p, whereas the overexpression of STAT3 abolished the suppressive effect of curcumin on this signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overexpression of STAT3 reversed the inhibitory effects of curcumin on the viability, migration and invasion of TPC-1 cells. It has been reported that suppression of STAT3 activity or expression inhibits human cancer progression ( 55 , 63 , 64 ). Curcumin has been demonstrated to promote PTC cell apoptosis by increasing DNA damage, endoplasmic reticulum stress and the PI3K/Akt signaling pathway ( 16 , 42 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is a critical signal protein that is involved in a variety of growth factors and cytokines, which triggers a variety of biological outcomes, including cell growth, differentiation, and survival [ 11 ]. Moreover, STAT3 is reported to be an important oncogene in many malignant tumors.…”
Section: Introductionmentioning
confidence: 99%